Reingeniería de procesos en la empresa de empanadas El Huaso Chileno del cantón Rumiñahui, provincia de Pichincha - Jurado Sánchez, Jorge Aníbal (2015)
The objective of this research was to conduct a situational analysis to the company "El HuasoChileno" in order to establish the requirement for process reengineering the family business of processing and marketing of pies " El HuasoChileno " to which first a survey of 100 people (58 men and 42 women) to determine the needs of consumers for the product (external customer) and set the staffing situation and its outlook for the current situation was fabricated company (internal customers). Subsequently a situational analysis of the company was conducted, determining a historical account, location, also an analysis of the external environment was conducted by applying the PEST yielded information on the situation of the macro and the same way in environmental analysis performed using The tool is known as the study of Porter's five forces, in order to know the characteristics of the competitors, substitute products, customers and suppliers. All this information allowed the SWOT matrix structure. A key aspect of the research was to identify business processes, starting with the organizational structure, products and services offered, meet production processes, the inputs used in making the product, as the administrative process handled, marketing and marketing. Based on the information gathered we proceeded to make a proposal for process reengineering, first setting the strategic direction of the company, with a proposed mission, vision, objectives, principles, values. The value chain is then determined, the established process map, identifying the critical points was performed by characterizing the processes, modeling processes identified times was made; Likewise, graphing of improved company processes are carried out to establish the definition of the proposed new organizational structure for the company. Finally the budget at an estimated cost of $ 9,700, for the implementation of the processes and the development of products that help the company to become more efficient and more competitive in the market where it operates was determined